2015
DOI: 10.1111/ejn.13122
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation enhances the effects of motor imagery training in a finger tapping task

Abstract: Motor imagery (MI) training and anodal transcranial direct current stimulation (tDCS) applied over the primary motor cortex can independently improve hand motor function. The main objective of this double-blind, sham-controlled study was to examine whether anodal tDCS over the primary motor cortex could enhance the effects of MI training on the learning of a finger tapping sequence. Thirty-six right-handed young human adults were assigned to one of three groups: (i) who performed MI training combined with anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Based on recent findings by Saimpont et al . 30 , however, coupling MIP with tDCS applied over M 1 resulted in significant greater performance compared to tDCS alone. Finally, other experimental conditions should ideally be included in future experimental designs to adequately frame and conclude about the relevance of combining MIP and tDCS.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Based on recent findings by Saimpont et al . 30 , however, coupling MIP with tDCS applied over M 1 resulted in significant greater performance compared to tDCS alone. Finally, other experimental conditions should ideally be included in future experimental designs to adequately frame and conclude about the relevance of combining MIP and tDCS.…”
Section: Discussionmentioning
confidence: 88%
“…Using a finger sequential task, Saimpont et al . 30 further showed that MIP contributed to improve performance, however with results when tDCS was simultaneously applied over M 1 . Yet, only these two experimental studies focusing on upper-limb motor performance investigated the combined effect of both tDCS and MIP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Additional studies have revealed significant benefits of tDCS on SFTT learning. Interestingly, the number of correctly executed sequences increased both when M1-tDCS was applied concurrently with performance (Saucedo Marquez et al, 2013), and when tDCS was applied during motor imagery of sequences (Saimpont et al, 2016). When individuals received M1-atDCS during performance, RTs decreased during training (Stagg et al, 2011), whereas when M1-atDCS was applied between two training sessions, reduced execution time of correct sequences was found during early consolidation (Tecchio et al, 2010), i.e., stabilization of the motor memory rapidly after its initial acquisition (Brashers-Krug et al, 1996).…”
Section: Modulating Motor Learning Processes Through Tdcsmentioning
confidence: 99%